Skeletogenesis of Myiopsitta monachus (Psittaciformes) and sequence heterochronies in Aves. Issue 1 (21st November 2016) - Carril, Julieta; Tambussi, Claudia P.
SUMMARY: The ossification sequence of Myiopsitta monachus was determined. Myiopsitta has a similar sequence to other altricial birds, with delayed skeletons compared to precocial species. The hindlimbs ossify before the forelimbs, a condition that could be linked to altriciality. To determine the stability of the sequences of ossification across birds, we selected species of different groups of Aves and used event‐pairing method and character mapping on a phylogeny. Our results show that the homogeneity in the development of birds was supported by 56.77% of the character states. Event‐pair cracking phylogenetic method was applied to identify sequence heterochronies. Results reveal a high number of heterochronies and show that the long bones in limbs may behave as modules. In Myiopsitta, the ossa ectethmoidale and mesethmoidale ossify early. These bones provide the origin site of the Psittaciformes' novel adductor m. ethmomandibularis, associated with strong bite forces, and its acceleration in the sequence may correspond to the functional hypothesis. Also, the early appearance of some hyoid apparatus elements occurs, and could be related to the development of tongue in Psittaciformes and its role in handling food, and is in concordance with the functional and size hypothesis.